KEBIJAKAN KEPEMIMPINAN PENDIDIKAN - Riza Mahara (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
In general, the definition of leadership can be formulated as follows, "leadership means the ability and readiness possessed by someone to be able to influence, encourage, invite, guide, move, direct, and if necessary force people or groups to accept this influence and then do something that can help achieve a certain goal that has been set. Leadership is a contribution from someone in a cooperative situation. Leadership and groups are two things that cannot be separated from one another. There is no group without leadership, and conversely leadership only exists in situations of group interaction, a person cannot be said to be a leader if he is outside the group, he must be in a group where he plays the roles and activities of his leadership activities. To get the right research results, we need an approach and type of research, this type of research as a way to gain knowledge or solve problems faced in accordance with the formulation of the problem. Solving the problems faced of course there are similarities and differences in ways to solve them. In this study the authors used a descriptive method, namely "a method that describes existing phenomena, both natural and human engineering. From the results of interviews conducted by researchers with teachers, it can be concluded that teachers prefer it when the principal holds meetings with dialogue and discussion even though the reprimands by the principal are sharper and more extreme. Discipline coaching is often carried out in work meetings every semester and at the end of the school year, so that at the beginning of the semester and the beginning of the school year class teachers and fields of study are ready to carry out their duties